Toward a New Theory of Moderate Contingentism: Individuals just are Realized Essences. - Gricius, Pranciškus (Problems / Problemos, 2022)
In this paper, we propose a new actualist and contingentist modal metaphysics - fundamental essentialism - according to which individuals just are realized essences. Orthodox possible worlds semantics is incompatible with actualism and contingentism since Kripke models in which paradigmatic contingentists propositions are true require possible worlds whose domain contain merely possible individuals. In light of this problem, Plantinga has developed modal metaphysics based on essences, but it has been claimed by Fine, Williamson, and others, that it cannot be upheld because of the problem of unexemplified essences. We answer the latter problem by claiming that individuals just are realized essences. Then, justifying our theory further we refute Williamson's deductive argument for necessitism. Afterward, we show in what sense fundamental essentialism is contingentist metaphysics.